A new genus, three new species and a new species record of Epipaschiinae (Lepidoptera: Pyralidae) from India - Ranjan, Rahul; Singh, Navneet; Kirti, Jagbir Singh (Zootaxa, 2022)
In the present manuscript, a new genus Atkinomus Ranjan, N. Singh & Kirti, gen. nov. is established and described for a new species Atkinomus parilis Ranjan, N. Singh & Kirti, sp. nov. from Sikkim, India. Additionally, two new species, Arcanusa confusa Ranjan, N. Singh & Kirti, sp. nov. (Sikkim) and Lamida whitakeri Ranjan, N. Singh & Kirti, sp. nov. (Sikkim, Uttarakhand) are described. Lamida buruensis Janse, 1931 is reported for the first time from India. Differential diagnoses and photographs of adults and male genitalia are provided.